Bullying em adolescentes: influência da inteligência e da competência social na sua incidência - Guedes, Deborah Zacarias [UNIFESP] (2018)
Bullying is unwanted, aggressive behavior, with the usage of force, threat, or coercion to abuse or intimidate school aged children. It is a repeated and intentional action that carries an imbalance of social or physical power. Boys practice direct bullying (verbal and physical) more than girls that deal with the indirect form (subjective actions). The consequences will depend on the frequency, duration and severity of the aggression, but it is common to find socialization problems, academic, physical and emotional disorders. School is a set for consolidation of knowledge and affective exchanges with friends, but it is also the place of greater incidence of bullying in adolescence, which is a period of neural architecture reorganization, physical transformation, emotional oscillation, search for autonomy and identity, impulsive transgressor and risk behavior with omnipotence fantasies. Internal protection factors such as Intelligence and Social Competence are used to reduce vulnerability and promote resilience. Fluid intelligence is the adolescent's ability to understand, solve problems and gain insights in new situation, with little prior information. Social competence is perceived through adolescents' performance in sociability, academic performance and taking part in activities. A cross-sectional study was conducted with 507 adolescents (11 to 17 years old), both sexes, in elementary school-2 and high school, in public and private schools. A socioeconomic and demographic questionnaire was applied. The incidence of Bullying was measured by the School Bullying Assessment Scale - EAB-E. Intelligence was assessed by the Raven Progressive Matrices - General Scale and Social Competence through the Youth Self Report - YSR. Of the 507 adolescents surveyed, 161 were involved in bullying (31.8%), of which 35 were victims, 110 were aggressors and 16 were victim-agressor. Victims preponderated at 12 years (boys) and 15 years (girls). Family income was above 5 minimum wages. Caucasian, eutrophic majority belonged to groups, cohabiting with both parents, Christians, more than 5 friends and maternal schooling in high school (for students of public schools) and higher maternal education (for students of private schools). School type does not interfere in the occurrence of bullying and boys were more aggressive (42.2%). Girls prevail as victims (11.2%) and victim-aggressors (6.8%). Incidence of those involved in bullying is higher in boys (37.5%), especially in elementary school-2 (40%). Bullying, Intelligence and Social Competence are independent statistical variables. However, there is a tendency for an inverse correlation among Victim and Social Competence and positive correlation with student's schooling. Victim-aggressor presents correlation with Competence in Activity, Social Competence and Maternal schooling.